Trioecy is maintained as a time-stable mating system in the pink sea urchin Toxopneustes roseus from the Mexican Pacific - Julia Patricia Díaz-Martínez; Leobarda Margarita Mejía-Gutiérrez; Valentina Islas-Villanueva; Francisco Benítez-Villalobos (Scientific Reports, 2022)
Abstract Trioecy is a sexual system that consists of the co-occurrence of females, males and hermaphrodites in a population and is common in plants; however, in animals it is uncommon and poorly understood. In echinoderms, trioecy had never been recorded until now. Frequencies of females, males, and hermaphrodites were evaluated and gametogenic development was histologically characterized in a population of Toxopneustes roseus inhabiting the Mexican Pacific. Trioecy in this population is functional and temporally stable, since the three sexes coexisted in each sampling month. The hermaphrodites presented similar gametogenic development as the females and males and participated during the spawning season, contributing to the population’s reproductive process. Trioecy is considered an evolutionarily transitory state, and it is extremely difficult to explain its presence in a species. We hypothesize that continuous ocean warming represents a threat to the survival of this population of T. roseus, since its early developmental stages, which represent a population bottleneck, are more vulnerable to high temperatures than other sea urchins inhabiting the area, while its population density is significantly lower. These conditions generate a strongly stressed environment, which is the determining factor that maintains the stability of trioecy in the species in which it has been studied.